2019
DOI: 10.1186/s41241-018-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of epidermal growth factor receptor (EGFR) expression in prostatic acinar adenocarcinoma

Abstract: Background: Epidermal growth factor receptor (EGFR) is potential prognostic biomarker expressed in many human cancers. Prognostic significance of EGFR immunohistochemical expression has not been established in prostatic acinar adenocarcinoma, therefore we aimed to evaluate the frequency of expression of EGFR in prostatic adenocarcinoma and its association with other prognostic parameters. Methods: The study included 123 cases of biopsy proven prostatic acinar adenocarcinoma treated at Liaquat National hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Even more, castration leads to an increase in EGFR expression [96]. Supporting this crosstalk between AR and EGFR, several studies have found a significant relationship between EGFR expression and PCa progression [96][97][98][99][100][101][102]. In this study, no correlation was found in this direction.…”
Section: ãããmentioning
confidence: 48%
“…Even more, castration leads to an increase in EGFR expression [96]. Supporting this crosstalk between AR and EGFR, several studies have found a significant relationship between EGFR expression and PCa progression [96][97][98][99][100][101][102]. In this study, no correlation was found in this direction.…”
Section: ãããmentioning
confidence: 48%
“…Aberrant EGFR expression was frequently detected in prostate cancer tissues associated with high-grade advanced stages ( Schlomm et al., 2007 ; Hashmi et al., 2019 ), suggesting EGFR may play a mechanistic role in the progression of prostate cancer. Therefore, EGFR-targeted therapy can be a potential treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of EGFR signaling has been implicated in normal prostate growth and neoplastic development (Kambhampati et al, 2005). Histological examination of EGFR expression in prostatic cancer tissues revealed that EGFR was overexpressed in 18-30% of adenocarcinoma and significantly associated with high Gleason score, high serum prostate-specific antigen (PSA), and worse outcomes (Di Lorenzo et al, 2002;Schlomm et al, 2007;De Muga et al, 2010;Hashmi et al, 2019), implicating its role as a prognostic biomarker in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Histologic parameters that predict prognosis include gleason score, tumor volume (tumor quanti cation), extra-prostatic soft tissue/fat involvement, seminal vesicle invasion, perineural and lympho-vascular invasion [3]. Besides these well-de ned histologic parameters, biomarkers such as, ERG, PTEN, FSN and androgen receptor (AR), also possess some prognostic value, but their routine use is not considered justi ed in all patients, up till now [4][5][6][7]. Among above-mentioned pathologic prognostic parameters, gleason score is given much importance in pathological reporting.…”
Section: Introductionmentioning
confidence: 99%